Harmonizing Religious Science and Technology Through Boarding School System: A Case at a State Islamic Senior High School - Syaifuddin, Mohammad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The increased number of Islamic educational institutions in Indonesia, which has not been matched by an improvement in education quality, is the impetus for this study. There are still several Islamic educational institutions that have not been able to adequately integrate religious knowledge with science and technology. This is the objective of the boarding school program of the State Islamic Senior High School (Madrasah Aliyah Negeri) Insan Cendekia Pekalongan. This study seeks to present the implementation model of student activity programs based on scientific harmonization at MAN Insan Cendekia Pekalongan boarding school. Field research was utilized in this qualitative research design. This study's informants include the Head of Madrasah, the Deputy Head of Curriculum, the Deputy Head of Student Affairs, the Deputy Head of Dormitory, and students in the tenth grade. The researcher obtained information via interviews, observations, and documentation. In the meanwhile, the researcher verified the accuracy of the data by triangulating data sources, observers, and hypotheses. The data is then evaluated using reduction techniques, presentation, and data verification. According to the findings of this study, the implementation of student activity programs via the boarding school system at MAN Insan Cendekia Pekalongan adopts a separated integration system (SIS) paradigm.